Primary Endometrial Adenocarcinoma with Signet-Ring Cells: A Rarely Observed Case and Review of the Literature - Aslı Kahraman Akkalp; Eser Sefik Ozyurek; Umit Seza Tetikkurt; Senay Yalcin; Yazgi Koy; Abdullah Taner Usta (Case Reports in Obstetrics and Gynecology)
An extremely rare case of a “primary endometrial adenocarcinoma with signet-ring cells” is presented in this study with microscopical images of the characteristic coexistence of the tumour and intermediate precancerous areas containing signet-ring cells.